Medicinal plants in traumatic brain injury: Neuroprotective mechanisms revisited. (17th June 2019) - Keshavarzi, Zakieh; Shakeri, Farzaneh; Barreto, George E.; Bibak, Bahram; Sathyapalan, Thozhukat; Sahebkar, Amirhossein
Abstract: Traumatic brain injury (TBI) is the most prevalent health problem affecting all age groups, and leads to many secondary problems in other organs especially kidneys, gastrointestinal tract, and heart function. In this review, the search terms were TBI, fluid percussion injury, cold injury, weight drop impact acceleration injury, lateral fluid percussion, cortical impact injury, and blast injury. Studies with Actaea racemosa, Artemisia annua, Aframomum melegueta, Carthamus tinctorius, Cinnamomum zeylanicum, Crocus sativus, Cnidium monnieri, Curcuma longa, Gastrodia elata, Malva sylvestris, Da Chuanxiong Formula, Erigeron breviscapus, Panax ginseng, Salvia tomentosa, Satureja khuzistanica, Nigella sativa, Drynaria fortune, Dracaena cochinchinensis, Polygonum cuspidatum, Rosmarinus officinalis, Rheum tanguticum, Centella asiatica, and Curcuma zedoaria show a significant decrease in neuronal injury by different mechanisms such as increasing superoxide dismutase and catalase activities, suppressing nuclear factor kappa B (NF‐κB), interleukin 1 (IL‐1), glial fibrillary acidic protein, and IL‐6 expression. The aim of this study was to evaluate the neuroprotective effects of medicinal plants in central nervous system pathologies by reviewing the available literature.